Podmiotowość - jej znaczenie i wartość w pedagogice chrześcijańskiej - Marian Nowak (Nicolaus Copernicus University in Toruń, 2009)
The paper shows the problem of the subjectivity as the value introduced with the Christianity (one from many others) and is showing the education as one of the possibilities to helping the pupil to arriving to the ability: to be the author of his own acting and to be only one responsible for this activity. The subjectivity can be understand in different ways: as a value static or dynamic, as value functional and potential, and also as the initial subjectivity (given to each human been) and the final subjectivity (some time as a result of long life work and purpose of education and also the goal of work on his self). The subjectivity must and can be educated and it can be the principal purpose of the educators Work - to promote the work on his self. L. Jeleńska to this task rank the incrementing in the conscience of the pupil some values inspiriting him in his action. There are three task to fuelling in this direction: 1) bringing to the child some values; 2) producing the possibilities of self education; 3) reinforcing the possibilities to manage one self.